Simplified probabilistic evaluation of the variability of soil-structure interaction parameters on the elastic transmission of ground movements - El Kahi, Elio; Deck, Olivier; Khouri, Michel; Mehdizadeh, Rasool; Rahme, Pierre (Engineering structures, 2020)
[Display omitted] •Probabilistic approach quantifying the variability of SSI parameters on the Δ/Δ0.•Simplified elastic meta-model reflecting the structure response.•SA (3 procedures (local & global) one-way analysis, Sobol & McKay) using MCS & LHS.•Confidence intervals to be used by engineers when evaluating induced building damage. An efficient probabilistic approach is presented to consider the uncertainty related to the evaluation of the transmission of ground movements to structures considering the influence of the variability of the soil-structure interaction (SSI) parameters (namely the building stiffness EI/B, the soil modulus k and the structure length L). These movements can be produced by tunnels excavation, sinkholes, mining subsidence, etc. This probabilistic approach aims to quantify the relative importance of the variability of the main SSI parameters on the structure response via a sensitivity analysis (SA). The structure response is evaluated using analytical and numerical models. The analytical model is applied using Mathematica where the structure is modeled by an elastic Euler-Bernoulli beam and the soil by a combination of elastic springs as per the Winkler model. The numerical model is developed using Plaxis 2D coupled with the programming tool Python for a significant number of numerical simulations to validate the analytical results obtained. The objective is to evaluate the impact of the parameters variability which are assumed to be of a random nature. To avoid time and computation difficulties, a simplified analytical meta-model that reflects the structure response is proposed. Based on this meta-model, the SA is performed using three selected procedures, one local and two global, namely, one-way analysis, Sobol and McKay respectively. Results reveal the contribution of each input parameter on the variability of the response using various sampling techniques, such as random Monte-Carlo Simulations (MCS) and Latin Hypercube Sampling (LHS). Accordingly, the effect of EI/B increases with the increasing values of the relative stiffness (ρ*); however, the effect of k increases when ρ* decreases. Results also reveal the influence of the variability of the main SSI parameters on the rate of the ground movement that is transmitted to structures; confidence intervals are set and can be used by engineers and designers when evaluating the induced building damage in response to the transmission of ground movements taking into consideration these uncertainties.